Changing Attitudes Through Social Influence: Does Social Distance Matter?. Issue 1 (2nd January 2016) - Mahaffey, Amanda L.; Bryan, Angela D.
ABSTRACT: To test the effects of social influence and social distance on attitudes, we assessed judgments of gay and lesbian targets in various contexts over three studies ( n = 814, 51% female). We compared the impact of a derogatory message to a relatively favorable message ostensibly written by another participant. Participants were robustly moved by the feedback; social influence was a significant predictor in final evaluations of the target, as was social distance. Discrimination against gay men and lesbian women appears not to be a fixed behavior; seemingly anyone can be persuaded to discriminate or not to discriminate by mere peer suggestion.